Examining the role of ‘ulamā in the Islamization process of the Malay World - Abdul Jalil, Mohd Noh; Mohd Nor, Mohd Roslan (International Islamic University Malaysia, 2020)
This article analyses the roles of ‘ulamā’ in propagating the message of Islam in the Malay world. Islam managed to reach many corners of the Malay world in the 17th century. Evidence has indicated that ‘ulamā’ were among those who had participated actively in propagating the messages of Islam to the local people. Classical Malay texts served as the best available records to understand the roles of these ‘ulamā’ at that time. Hence, analysis are made on selected classical Malay texts in order to understand the actual roles played by the ‘ulamā’ in the Malay world at that time in transforming the understanding of the local Malay people from the beliefs in Hindu-Buddhist and animism to Islam. Three significant roles of the ‘ulamā’ at that time have been identified namely propagating knowledge to the local people, religious advisors to the rulers as well as engaging with the non-Muslims.